Advances in quantum chemistry - Sabin, John R.; Brandas, Erkii; ScienceDirect eBooks (London : Academic Press, 2005)
Advances in Quantum Chemistry presents surveys of current developments in this rapidly developing field that falls between the historically established areas of mathematics, physics, chemistry, and biology. With invited reviews written by leading international researchers, each presenting new results, it provides a single vehicle for following progress in this interdisciplinary area. This volume continues the tradition with high quality and thorough reviews of various aspects of quantum chemistry. It contains a variety of topics that include an extended and in depth discussion on the calculation of analytical first derivatives of the energy in a similarity transformed equation of motion couples cluster method.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Quantum chemistry; Chemistry, Physical and theoretical; Chemistry, Physical and theoretical; Quantum chemistry; Electronic books